Semantic Analysis in Modern Arabic Vocabulary Learning - Cahaya Khadijah; Fadilah Nur Azizah; Ahmad Nur Mizan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study discusses the application of semantic analysis in modern Arabic vocabulary learning. The study aims to explain the role of semantics in helping learners understand the meaning of vocabulary accurately according to its context of use in modern communication. The research employed a qualitative approach using library research by collecting data from various journals, books, and scientific articles related to semantics and Arabic language learning. Data collection techniques were conducted through documentation studies, while data analysis used a descriptive-analytical method. The results of the study indicate that semantic analysis plays an important role in improving the understanding of modern Arabic vocabulary, especially in understanding lexical meanings, contextual meanings, synonyms, and changes in meaning caused by social, cultural, and digital technological developments. The semantic approach also helps learners use vocabulary in a more communicative, contextual, and modern-language-oriented manner. In addition, the application of digital media in vocabulary learning can support a more interactive understanding of meaning that is relevant to current communication needs. Therefore, semantic analysis becomes one of the effective approaches in improving the ability to understand and use modern Arabic vocabulary appropriately.